2020
DOI: 10.21873/invivo.12173
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic Immune-Inflammation Index Predicts Clinical Outcomes in Kidney Transplant Recipients

Abstract: Background: Outcomes after kidney transplantation (KTx) remain limited by delayed graft function (DGF) and acute rejection. Non-invasive biomarkers may help identify patients at increased risk for these events. We examined the association between the systemic immune-inflammation index (SII), a novel inflammatory biomarker, and outcomes after KTx and evaluated its ability to predict post-transplant prognosis. Patients and Methods: Adult patients who underwent primary KTx at our institution between 2016-2019 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Another retrospective study found the association between SII and increased TNM stage and poor prognosis of renal cell carcinoma patients undergoing radical nephrectomy ( 34 ). However, there have also been several studies that revealed the limitations of SII ( 35 , 36 ). A study that enrolled 378 patients who underwent primary kidney transplantation (KTx) in America reported that SII demonstrated limited utility as an independent predictor of outcomes after KTx, while in combination with other clinically relevant parameters, SII could be a useful predictor of prognosis after KTx ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another retrospective study found the association between SII and increased TNM stage and poor prognosis of renal cell carcinoma patients undergoing radical nephrectomy ( 34 ). However, there have also been several studies that revealed the limitations of SII ( 35 , 36 ). A study that enrolled 378 patients who underwent primary kidney transplantation (KTx) in America reported that SII demonstrated limited utility as an independent predictor of outcomes after KTx, while in combination with other clinically relevant parameters, SII could be a useful predictor of prognosis after KTx ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have also been several studies that revealed the limitations of SII ( 35 , 36 ). A study that enrolled 378 patients who underwent primary kidney transplantation (KTx) in America reported that SII demonstrated limited utility as an independent predictor of outcomes after KTx, while in combination with other clinically relevant parameters, SII could be a useful predictor of prognosis after KTx ( 35 ). Another meta-analysis with 2,693 subjects included suggested that elevated SII indicated poor prognosis in patients with urinary system cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] SII index is the most tested and validated inflammation-based index since it provides an integrative evaluation of both immune and inflammatory activation, and its prognostic role has been documented in several groups of patients. [15][16][17][18][19][20] The role of SII in atherosclerotic disease and ischemic cardiomyopathy has been assessed by previous studies, [6][7][8] and a single SII Index determination appeared to significantly improve risk stratification of major cardiovascular events than traditional risk factors in CAD patients requiring PCI. 6 Off note, according to our analysis, patients with a higher SII at admission have a more severe CAD compared to those admitted with a low SII.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic plaque formation involves a large number of cells, such as macrophages, T cells and several mediators of inflammation, 28 defining complex crosstalk between adaptive and innate immunity from the earliest stage of lesion development to ultimate clinical complications 1–5 . SII index is the most tested and validated inflammation‐based index since it provides an integrative evaluation of both immune and inflammatory activation, and its prognostic role has been documented in several groups of patients 15–20 . The role of SII in atherosclerotic disease and ischemic cardiomyopathy has been assessed by previous studies, 6–8 and a single SII Index determination appeared to significantly improve risk stratification of major cardiovascular events than traditional risk factors in CAD patients requiring PCI 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation